Pengaruh Komitmen Organisasi, Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Sumber Daya Insani (SDI) pada PT. Karya Maju Sejahtera Bersama - Liana Nanda Lestari; Alimatul Farida; Abdillah Mundir (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to determine the influence of organizational commitment, work motivation, and job satisfaction on human resource performance. This research is quantitative using a survey type and data analysis techniques using SPSS 25. The respondents for this research were 67 employees of PT. Karya Maju Sejahtera, Gudang B. The results of this research show that organizational commitment partially has no effect on human resource performance. Meanwhile, simultaneously these variables have no effect on the performance of PT. Karya Maju Sejahtera Bersama.